The impact of smoking during pregnancy on children's body weight - Kabir Dasgupta; Keshar M. Ghimire; Gail Pacheco (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2018)
We study the effect of mothers' smoking during pregnancy on children's body weight outcomes during pre-school ages using a nationally representative sample of children surveyed in NLSY79 Children and Young Adults. Exploiting 'within mother and across pregnancies' variation in smoking behavior, we find that maternal smoking during pregnancy has a negative effect on weight outcomes at birth but the children of mothers who smoked during pregnancy catch up with the children of non-smokers, usually within their first-year post birth. We also find evidence to suggest that children of smokers in later pre-school ages (3 to 5 years old) are likely to have higher weight outcomes relative to children of non-smokers when their mother reported higher intensity levels of smoking (greater than one pack per day).
Keywords: I10; I12; I18; 330; Maternal smoking; Children's health outcomes; child weight; child BMI